A Rare Genetic Defect of MBL2 Increased the Risk for Progression of IgA Nephropathy - Ouyang, Yan; Zhu, Li; Shi, Manman; Yu, Shuwen; Jin, Yuanmeng; Wang, Zhaohui; Ma, Jun; Yang, Meng; Zhang, Xiaoyan; Pan, Xiaoxia; Ren, Hong; Wang, Weiming; et al. (Frontiers in Immunology, 2019)
The aim of this study was to investigate the association between lectin pathway-related genetic variations and progression in IgA nephropathy. Biopsy-proven IgAN patients with eGFR ≥15 ml/min/1.73 m2 at baseline and a minimum follow-up of 12-months were enrolled. A total of 1,007 patients and 121 healthy controls were enrolled from two Chinese renal centers. The discovery cohort consisted of 606 patients, and the validation cohort consisted of 401 patients. First, promoters, all exons and their boundary regions of MBL2 and FCN2 were sequenced in 50 patients, and then 37 variations were identified. Of these variations, 7 expression-associated variations were selected and genotyped in the whole discovery cohort. We found that rs1800450 in MBL2 and rs7851696 in FCN2 were associated with an increased risk for ESRD as well as serum MBL or L-ficolin levels. However, only rs1800450 was successively validated for its association with ESRD (HR, 15.91; 3.27–77.34; P = 0.001) in the fully adjusted model in the validation cohort. In addition, 2.7% of patients, and 2.5% of healthy controls carried rs1800450-AA. IgAN patients with rs1800450-AA lacked expression of MBL in both serum and renal tissue and had more severe tubulointerstitial damage. Furthermore, a combined effect of rs1800450-AA with a previously reported clinical risk score was observed in which patients with both a high clinical risk score (≥1%) and rs1800450-AA had a strikingly increased 10-years ESRD risk by 37.1-fold (7.17 to 192.13-fold). In summary, IgAN patients carrying MBL2 rs1800450-AA have a high risk for renal function deterioration, probably due to inactivation of the complement MBL pathway.